2015
DOI: 10.1152/jn.00188.2015
|View full text |Cite
|
Sign up to set email alerts
|

Rod- and cone-driven responses in mice expressing human L-cone pigment

Abstract: Tsai TI, Atorf J, Neitz M, Neitz J, Kremers J. Rod-and cone-driven responses in mice expressing human L-cone pigment. J Neurophysiol 114: 2230 -2241, 2015. First published August 5, 2015 doi:10.1152/jn.00188.2015.-The mouse is commonly used for studying retinal processing, primarily because it is amenable to genetic manipulation. To accurately study photoreceptor driven signals in the healthy and diseased retina, it is of great importance to isolate the responses of single photoreceptor types. This is not eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 55 publications
3
18
0
Order By: Relevance
“…Details regarding the extraction and analysis of major components have been published previously: flash ERGs, 2 flash OPs, 33 sawtooth flicker ERG, 34 sinusoidal flicker ERG. 35 Briefly, (1) the STR was defined as the positive (pSTR) peak to negative (nSTR) trough (at approximately 120 and 220 ms after stimulus onset, respectively). (2) In the scotopic flash ERG, the a-wave was defined as the difference between baseline and the minimum within 50 ms post stimulus onset, and the b-wave was the difference between the a-wave minimum and the b-wave maximum after digital removal of OPs in the Fourier frequency domain from the leading ascending limb with a square, 50-to 300-Hz band-pass filter.…”
Section: Signal Analysismentioning
confidence: 99%
“…Details regarding the extraction and analysis of major components have been published previously: flash ERGs, 2 flash OPs, 33 sawtooth flicker ERG, 34 sinusoidal flicker ERG. 35 Briefly, (1) the STR was defined as the positive (pSTR) peak to negative (nSTR) trough (at approximately 120 and 220 ms after stimulus onset, respectively). (2) In the scotopic flash ERG, the a-wave was defined as the difference between baseline and the minimum within 50 ms post stimulus onset, and the b-wave was the difference between the a-wave minimum and the b-wave maximum after digital removal of OPs in the Fourier frequency domain from the leading ascending limb with a square, 50-to 300-Hz band-pass filter.…”
Section: Signal Analysismentioning
confidence: 99%
“…9,10,38 The increased difference between the maximal spectral sensitivities of the rods (498 nm) and the L*-cone pigment (561 nm) results in larger possible rod (75%) and L*-cone (55%) contrast and thus leads to larger ERG responses. 37 We further found that rod-and L*-cone-driven responses can be separated in the LIAIS mouse over a luminance range of three orders of magnitude. Rod-driven responses could be measured up to mean luminances of 7 cd/m 2 (corresponding to 7 3 10 3 photoisomerizations/sec).…”
mentioning
confidence: 57%
“…Different studies confirm that the substitution of the murine M-cone opsin by the L*-cone opsin results in a shift of the spectral sensitivity of the cones toward longer wavelengths with a maximum sensitivity at about 561 nm instead of 508 nm 36,39,40 without altering the cones' structure and function. 10,37 Tsai et al 37 described rod-and cone-driven responses in the LIAIS mice using the silent substitution technique and showed that they can be studied with large signal-to-noise ratio (SNR).…”
Section: Methods Experimental Animalsmentioning
confidence: 99%
See 2 more Smart Citations